The Protective Role of HLA-DRB113 in Autoimmune Diseases - Andreia Bettencourt; Cláudia Carvalho; Bárbara Leal; Sandra Brás; Dina Lopes; Ana Martins da Silva; Ernestina Santos; Tiago Torres; Isabel Almeida; Fátima Farinha; Paulo Barbosa; António Marinho; et al. (Journal of Immunology Research)
Autoimmune diseases (AIDs) are characterized by a multifactorial aetiology and a complex genetic background, with the MHC region playing a major role. We genotyped for HLA-DRB1 locus 1228 patients with AIDs-213 with Systemic Lupus Erythematosus (SLE), 166 with Psoriasis or Psoriatic Arthritis (Ps + PsA), 153 with Rheumatoid Arthritis (RA), 67 with Systemic Sclerosis (SSc), 536 with Multiple Sclerosis (MS), and 93 with Myasthenia Gravis (MG) and 282 unrelated controls. We confirmed previously established associations of HLA-DRB115 (OR = 2.17) and HLA-DRB103 (OR = 1.81) alleles with MS, HLA-DRB103 with SLE (OR = 2.49), HLA-DRB101 (OR = 1.79) and HLA-DRB104 (OR = 2.81) with RA, HLA-DRB107 with Ps + PsA (OR = 1.79), HLA-DRB101 (OR = 2.28) and HLA-DRB108 (OR = 3.01) with SSc, and HLA-DRB103 with MG (OR = 2.98). We further observed a consistent negative association of HLA-DRB113 allele with SLE, Ps + PsA, RA, and SSc (18.3%, 19.3%, 16.3%, and 11.9%, resp., versus 29.8% in controls). HLA-DRB113 frequency in the AIDs group was 20.0% (OR = 0.58). Although different alleles were associated with particular AIDs, the same allele, HLA-DRB113, was underrepresented in all of the six diseases analysed. This observation suggests that this allele may confer protection for AIDs, particularly for systemic and rheumatic disease. The protective effect of HLA-DRB113 could be explained by a more proficient antigen presentation by these molecules, favouring efficient clonal deletion during thymic selection.